1996
DOI: 10.1002/(sici)1099-1352(199634/12)9:5/6<368::aid-jmr267>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Membrane microstructural templates for enzyme domain formation

Abstract: Soluble proteins can spontaneously self-organize into two-dimensional domains at membrane interfaces, given sufficient mobility and specificity to membrane-localized ligands. The authors' recent results studying interfacial domain formation of the membrane-active enzyme, phospholipase A2, indicate that lateral phase separation of heterogeneous membrane mixtures creates anionic templates of specific morphology onto which the enzyme deposits, forming large protein assemblies. Selective removal of membrane compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Several previous studies have shown that PLA 2 hydrolysis products can form ordered structure domains in DPPC monolayers, , suggesting that the alignment of the products can provide enough energy reward to overcome the energy penalty caused by the electrostatic repulsion between anionic fatty acids. In addition, we believe that the further development of 3-D layer structure (Figure c) is also thermodynamically favorable because previous studies have shown that both C16 fatty acid (palmitic acid) and C16 lysolipid can align to form 3-D crystals. The existence of the crystals suggests that the energy reward obtained by the alignment to form 3-D structure is larger than the energy penalty caused by not only the electrostatic repulsion between anionic fatty acids but also the potential exposure of the hydrophobic acyl chains to water during the development of the layer above the original membrane plane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have shown that PLA 2 hydrolysis products can form ordered structure domains in DPPC monolayers, , suggesting that the alignment of the products can provide enough energy reward to overcome the energy penalty caused by the electrostatic repulsion between anionic fatty acids. In addition, we believe that the further development of 3-D layer structure (Figure c) is also thermodynamically favorable because previous studies have shown that both C16 fatty acid (palmitic acid) and C16 lysolipid can align to form 3-D crystals. The existence of the crystals suggests that the energy reward obtained by the alignment to form 3-D structure is larger than the energy penalty caused by not only the electrostatic repulsion between anionic fatty acids but also the potential exposure of the hydrophobic acyl chains to water during the development of the layer above the original membrane plane.…”
Section: Resultsmentioning
confidence: 99%
“…Several model membrane studies have shown the formation of new phase domains after the PLA 2 hydrolysis reaction. Using microcopy, some studies have directly observed the formation of new domains in phosphatidylcholine [1,2-dipalmitoyl- sn -glycero-3-phosphocholine (DPPC)] monolayers, and the newly generated domains can attract fluorescently labeled PLA 2 to bind and possibly provide feedback control for the hydrolysis reaction. ,,, Other studies have suggested that these domains appearing after PLA 2 hydrolysis are composed of the lipid substrate and the hydrolysis products (lysolipids and fatty acids). However, the aforementioned studies ,,, investigated PLA 2 activity at air–water interfaces of monolayers, and the formation of PLA 2 -binding phase domains has not been demonstrated in lipid bilayer systems. Some atomic force microscopy (AFM) studies have shown that supported lipid bilayers containing DPPC can have significant morphology changes after PLA 2 hydrolysis. One interesting observation is the appearance of three-dimensional (3D) crystalline structure domains with heights of 10–20 nm. ,, However, the function of these crystalline structure domains and the conditions for the formation are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, lateral domains result from the presence of specific lipids like cholesterol (37), ceramide (38), lysobisphosphatidic acid (39), or proteins like phosphatidylinositol transfer proteins (40) or bacteriorhodopsin (41). The presence of defects or domains in the bilayer structure may act as starting points for the enzyme activity (42)(43)(44)(45), entry of bacteria (46), budding and fission (47,48), or apoptosis (49). Microdomains have also been suggested to affect membrane permeability and from a pharmacological point of view play a key role in the phenomenon of drug-enhanced adsorption (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Hille et al have previously suggested ''superactivation'' of PLA 2 to be caused by the formation of PLA 2 aggregates at interfaces (18), and this was concluded also by Dennis and co-workers (19). Aggregation of PLA 2 caused by FFA has been demonstrated in 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) monolayers (20)(21)(22). The detailed characteristics of the enzyme aggregate have not been addressed.…”
Section: Introductionmentioning
confidence: 99%